Elevation affects both the occurrence of ungulate browsing and its effect on tree seedling growth for four major tree species in European mountain forests - Bernard, Marianne; Barrere, Julien; Morin, Xavier; Saïd, Sonia; Boulanger, Vincent; Granda, Elena; Benavides, Raquel; Jactel, Hervé; Heurich, Marco; García Rabasa, Sonia; Valladares, Fernando; Kunstler, Georges (Annals of Forest Science, 2024)
Financial support was provided by the European Union with the project BACCARA (FP7-226299, 7FP) and the Spanish Ministry for Innovation and Science with the grant Consolider Montes (CSD2008_00040). This study was funded by the French National Forest Office (ONF), French Office for Biodiversity (OFB) and National Centre for Scientific Research (CNRS) under partnership agreement 2016/05/6171. XM received support from the project DISTIMACC (BGF, ECOFOR 2014–23). GK received support from the REFORCE - EU FP7 ERA-NET Sumforest 2016 through the call ‘Sustainable forests for the society of the future’, with the ANR as national funding agency (grant 408 ANR-16-SUMF-0002) and from the ANR DECLIC (grant ANR-20-CE32-0005-01). Key message In European mountain forests, the growth of silver fir (Abies alba Mill.), sycamore maple (Acer pseudoplatanus L.), European beech (Fagus sylvatica L.) and Norway spruce (Picea abies (L.) H. Karst.) seedlings is more strongly affected by ungulate browsing than by elevation. But, the constraint exerted by ungulates, in particular the probability for seedlings to be browsed, increases with elevation for most species. Context While concerns about mountain forest regeneration rise due to their high vulnerability to climate change, the increase in wild ungulate populations and the expansion of their range in the last decades exert an additional constraint on the survival and growth of young trees. Understanding how this constraint can vary with elevation is thus a key to assess the consequences of this population increase for the regeneration of mountain forests. Aims In this study, we investigate the effect of elevation on (i) the occurrence of browsing for seedlings and on (ii) the reduction in seedling growth induced by ungulate browsing. Methods We monitored height growth and browsing occurrence on silver fir, sycamore maple, European beech and Norway spruce seedlings across seven elevation gradients (from 400 to 2013 m) located from France to northern Sweden. Results Seedlings of the two ...